EXCESSO DE PESO AO LONGO DO CICLO VITAL, CONSUMO DE BEBIDAS RICAS EM AÇÚCARES DE ADIÇÃO, FATORES DE RISCO METABÓLICOS E ASMA EM ADULTOS JOVENS: COORTE DE NASCIMENTO DE RIBEIRÃO PRETO – SP (1978-1979) - PADILHA, Luana Lopes (2018)
Epidemiological studies have been presenting relevant associations involving overweight, consumption of sugar-sweetened beverages (SSBs), metabolic risk factors for nontransmittable diseases, and asthma. However, mechanisms involved in these interrelationships have not yet been elucidated. In this way, epidemiological tools such as structural equation modeling (SEM) and the inverse-weighting of probability in marginal structural models, that insofar have not been used in scientific literature to investigate these relationships, can aid on the exploration of these variables. Chapter one of this thesis was the original article: “Lifetime overweight and its association with adult asthma: 1978/79 Ribeirão Preto Birth Cohort, São Paulo, Brazil”, which had the objective of estimating the association between overweight throughout the life cycle and asthma in adults from the Birth Cohort of Ribeirão Preto, São Paulo, Brazil, 1978/79, using structural equation modeling. It was a prospective cohort study involving three segments of the Cohort (n = 2,603): birth (baseline) (1978/79), school age at 9/11 years of age (1987/89) and adulthood at 23/25 years of age (2002/04). We proposed a exploratory theoretical model assessed through SEM to analyze the effects of overweight throughout the life cycle on asthma in adults. The asthma outcome was a continuous latent variable, formed by three indicators with converging loads: medical diagnosis of asthma, presence of wheezing in the past 12 months and measurement of bronchial hyperresponsiveness. As results, we observed that parental obesity (CPtotal= 0.211; p<0.0001; CPdirect= 0.115; p=0.007) and overweight at school age (CPtotal= 0.565; p<0.0001; CPdirect=0.565; p<0.0001) were the variables throughout the life cycle associated with overweight in adult life. Parental obesity (CPdirect=0.105; p=0.047) and thinness at birth (CPtotal= - 0.124; p=0.009; CPdirect= -0.131; p=0.007) were the variables associated with the continuous variable of asthma in adults. The highest “current SES” protected from both overweight (CPdirect= -0.171; p=0.016) and the continuous variable asthma (CPtotal= -0.179; p=0.041; CPdirect= -0.182; p=0.039) in adult life. Chapter II of this thesis was the original article: “Association between sugar-sweetened beverages with metabolic risk factors forxx non-transmissible diseases and asthma in young adults: analysis using marginal structural models”, which aimed to analyze the association of consumption of SSBs with multiple metabolic risk factors, obesity, hypertension and asthma in young adults, using marginal structural models. It was a cross-sectional study involving the fourth follow-up of the cohort (n = 2,063). We used inverse probability weighting in marginal structural models, adjusted for indicators of socioeconomic status, smoking and physical activity practice, to evaluate the association of tertiles and quartiles with frequency of habitual consumption of SSBs with insulin resistance, waist-to-height ratio, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, arterial hypertension and asthma, according to sex. It was observed in men that the higher tertiles of frequency of consumption of sugar-rich beverages were associated with higher insulin resistance (Tertile of soft drinks: RP=1.40, 95% CI: 1.00-1.95; p=0.046; Quartile of soft drinks: RP=1.62, 95% CI: 1.16-2.26; p=0.005), high waist-height ratio (Tertile of SSBs: RP=1.23, 95% CI: 1.05-1.43; p=0.009) and low HDL-c levels (Tertile of SSBs: RP=1.20, 95% CI: 1.01-1.40; p=0.034; Quartile of SSBs: RP=1.20, 95% CI: 1.00- 1.43; p=0.049); and the higher tertiles of beverage consumption were marginally associated with asthma (Tertile of soft drinks: RP=1.48, 95% CI: 0.99 - 2.20; p=0.050; Tertile of SSBs: RP=1.44, 95% CI: 0.97-1.12; p=0.067). In women, the higher frequency of consumption of sugar-rich beverages was only associated with low levels of HDL-c (Tertile of soft drinks: RP=1.22, 95% CI: 1.04-1.43; p=0.017; Tertile of SSBs: RP=1.20, 95% CI: 1.02-1.39; p=0.019; Quartile of SSBs: RP=1.31, 95% CI: 1.11-1.54, p=0.001). Thus, the results of this thesis showed that parental obesity was the starting point for overweight pathways in childhood and adulthood, with an evident transgenerational effect. Overweight in scholars may be linked to overweight in the adult. Parental obesity and thinness at birth were risks for the continuous variable asthma in adult life. In addition, frequent exposure to SSBs showed an effect on increased insulin resistance, abdominal obesity, reduction of HDL-c, and asthma in men; and in women, on the reduced HDL-c. The importance of coordinated efforts to encourage the reduction of the consumption of these beverages and of the excess weight in order to prevent metabolic damage throughout the life was evidenced.